Effect of dietary protein to energy ratio on body composition, digestive enzymes and blood plasm components in Clarias gariepinus(Burchell, 1822) - Ali, M Z; Jauncey, K (Indian Journal of Fisheries, 2011)
Effect of dietary protein to energy ratio on body composition, digestive enzymes and blood plasm components in Clarias gariepinus(Burchell, 1822)